In Vivo Confocal Microscopy and Anterior Segment Optical Coherence Tomography Findings of Patients with Iridocorneal Endothelial Syndrome - Gülay Güler Canözer; Emine Tınkır Kayıtmazbatır; Esra Öztürk; Ayşe Bozkurt Oflaz; Banu Bozkurt (Türk Oftalmoloji Dergisi, 2024)
This case report aims to present the findings of in vivo confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS-OCT) in three patients with iridocorneal endothelial (ICE) syndrome. Three female patients 37, 50, and 57 years of age presented with complaints of unilateral visual impairment and elevated intraocular pressure (IOP). Biomicroscopy revealed unilateral pupil irregularities and anterior synechiae, and gonioscopy demonstrated synechiae in the iridocorneal angle. IOP was within normal limits with medical treatment in two patients, while one patient had an IOP of 44 mmHg despite maximal antiglaucomatous treatment. IVCM revealed large, polymorphic, and hyperreflective cells in the corneal endothelial layer of the affected eyes and normal corneal epithelium, stroma, and endothelium in the fellow eyes. AS-OCT findings were normal in healthy eyes, while the affected eye showed synechiae in the iridocorneal angle and a hyperreflective, thickened endothelial layer. The patient with refractory glaucoma underwent trabeculectomy surgery with 5-fluorouracil. In conclusion, IVCM and AS-OCT allow a detailed examination of endothelial cell abnormalities and iridocorneal membranes in ICE syndrome, which is characterized by unilateral pupil and iris irregularities and anterior synechiae mainly in women.